Future Directions of Intraoperative Radiation Therapy: A Brief Review - Paunesku, Tatjana; Woloschak, Gayle E. (Frontiers in Oncology, 2017)
The use of intraoperative radiation therapy (IORT) is increasing with the development of new devices for patient treatment that allow irradiation without the need to move the patient from the surgical table. At the moment, ionizing radiation in the course of IORT is supported most often by the use of mobile devices that produce electrons, kilo voltage X-rays, and electronic brachytherapy and the development of applicators suitable for delivery of radionuclides for short-term brachytherapy. The establishment of new treatment devices and protocols that can be foreseen in the future, e.g., the development of proton or heavy ion sources suitable for IORT or the establishment of new treatment protocols such as the use of IORT in combination with immune system modulators or radiosensitizing nanoparticles, could lead to a significant increase in the use of IORT in the future. This review discusses the still limited use of IORT at this point in time and hypothesizes about possible future approaches to radiotherapy.